Advances in Oral Biomacromolecule Therapies for Metabolic Diseases - Jiao, Qiuxia; Huang, Yuan; He, Jinhan; Xu, Yining (Pharmaceutics, 2025)
Metabolic diseases like obesity and diabetes are on the rise, and therapies with biomacromolecules (such as proteins, peptides, antibodies, and oligonucleotides) play a crucial role in their treatment. However, these drugs are traditionally injected. For patients with chronic diseases (e.g., metabolic diseases), long-term injections are accompanied by inconvenience and low compliance. Oral administration is preferred, but the delivery of biomacromolecules is challenging due to gastrointestinal barriers. In this article, we introduce the available biomacromolecule drugs for the treatment of metabolic diseases. The gastrointestinal barriers to oral drug delivery and strategies to overcome these barriers are also explored. We then discuss strategies for alleviating metabolic defects, including glucose metabolism, lipid metabolism, and energy metabolism, with oral biomacromolecules such as insulin, glucagon-like peptide-1 receptor agonists, proprotein convertase subtilisin/kexin type 9 inhibitors, fibroblast growth factor 21 analogues, and peptide YY analogues.